ASSESSMENT OF SELECTED PLANT EXTRACT AS EXTENDER ON SPERM VIABILITY AND FUNCTIONAL INTEGRITY OF RED SOKOTO BUCK DURING COLD STORAGE (FUDMA JOURNAL OF SCIENCES, 2025)
The use of plant-based extenders has gained interest due to their protective and antioxidant capacity. This study evaluates the effects of scent leaf (Ocimum gratissimum), onions (Allium cepa), lemongrass (Cymbopogon nardus), and celery (Apium graveolens) extracts on the viability and functional integrity of Red Sokoto buck semen during cold storage. Semen samples were collected from ten mature Red Sokoto buck, pooled, and diluted with tris egg yolk extender. In a completely randomized design, the pooled semen samples were divided into 5. The different plant extracts were added to each sample at 1.5ml/ 1 ml of semen sample with the exception of the control which only contain tris egg yolk extender. Samples were then stored at 4°C in the refrigerator for 7 days. After which it was evaluated for sperm viability (motility, livability and abnormalities) and sperm functional integrity (membrane integrity, acrosome integrity and semen concentration). The result showed no significant difference (P>0.05) in motility, livability, or functional integrity among the treatments. However, scent leaf and lemongrass exhibited a higher sperm motility and livability, while celery showed the lowest. Lemongrass extract had higher acrosome and membrane integrity, whereas onions showed the lowest. Sperm abnormalities were reduced across treatments, supporting the protective role of plant extracts in semen storage. This study suggests that plant-based extenders are effective in semen preservation and therefore may serve as cost-effective and bio secured alternatives to synthetic extenders, sustaining the quality of semen during cold storage and enhancing reproductive efficiency in Red Sokoto goats.
Keywords: Cold storage; Plant extract; Red Sokoto buck; Semen extender; Sperm viability